Accommodating strategies for preventing chronic lower extremity injuries - Bates, B. T. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Trauma or tissue damage is simply the result of applying too much stress to a tissue via an external load either directly or indirectly. The application of force to the system results in stress that can cause tissue damage, i.e., injury. The problem can be viewed from two perspectives as stated by Nahum and Melvin in the preface of their book Accidental Injury, Biomechanics and Prevention (1993). One perspective is that of the professionals involved in injury diagnosis and treatment while the other is that of engineers and scientists (especially biomechanists) interested in the mechanics of injury. Both perspectives are well documented/represented in the professional and scientific literature. Tissue damage/injury results when a tissue is stressed beyond some critical value/tolerance level. The stress is a result of the magnitude of the force, the type or direction of the force and the time interval between repetitive loading. Tissue damage can be acute (a single traumatic event) or chronic (developing/progressing over time). Most lower extremity injuries resulting from running and landing activities are chronic, resulting from repetitive loading to underdeveloped and/or unprepared structures. Chronic injuries can be avoided or minimized by adhering to a number of simple principles that are discussed in this paper.